Preparation of PEG Reinforced Bamboo Cellulose Acetate Membrane Materials and Its Properties - Celada, Ekiñe; Driller, Richard; Tiso , Marc (Journal of Green Energy and Environmental Engineering, 2025)
In this paper, cellulose was extracted from Dendrocalamus sinicus, a giant bamboo species specially distributed in southwest China. Bamboo cellulose acetate (BCA) was prepared by using acetic anhydride as acetyl agent and concentrated sulfuric acid as catalyst. Then the polyethylene glycol (PEG 200), a kind of non-toxic and non-irritating plasticizer, was used as additive to prepare cellulose acetate/polyethylene glycol composite membrane material. The properties of the polyethylene glycol reinforced membrane materials were studied by the methods of SEM, IR, tensile properties and contact angle. The results showed that the purity of the bamboo cellulose was 93.46%, the cellulose acetate acetyl content was 48.54%, and the degree of substitution was 1.99. PEG was successfully loaded on the cellulose acetate/polyethylene glycol composite membrane, the structure of cellulose acetate itself was not changed, and the inner structure of the composite membrane was more compact. The tensile strength and fracture elongation increased by 13.42% and 114.76% respectively. The UV barrier effect was better than that of the base membrane, the contact angle reduced from 93 to 28, and the hydrophilicity greatly increased. The thermal stability of the material was slightly reduced after the addition of PEG.